An introduction to critical reading - McCraney, Leah (Cengage Wadsworth Boston, 2011)
This unique college reading text gives students experience reading and evaluating poetry, short stories, essays, and textbook chapters. An innovative Instructor's Manual gives instructors a wealth of teaching ideas and background material on each piece with a focus on critical thinking